(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2019)
This article describes buccal permeation of chlorpheniramine maleate (CPM) and its transbuccal delivery using mucoadhesive buccal patches. Permeation of CPM was calculated in vitro using porcine buccal membrane and in vivo in healthy humans. Buc- cal formulations were developed with hydroxyethylcellulose (HEC) and evaluated for in vitro release, moisture absorption, mechani- cal properties, and bioadhesion, and optimized formulation was subjected for bioavailability studies in healthy human volunteers. In vitro flux of CPM was calculated to be 0.14 ± 0.03 mg.h−1.cm−2 and buccal absorption also was demonstrated in vivo in human vol- unteers. In vitro drug release and moisture absorbed were governed by HEC content and formulations exhibited good tensile and mu- coadhesive properties. Bioavailability from optimized buccal patch was 1.46 times higher than the oral dosage form and the results showed statistically significant difference.